Analysis of the influence of binding adhesives on the structural strength of integral and semi-rigid covers - Paliukh, Oleksandr; Kyrychok, Petro; Dziadyk, Yevhenii (Technology audit and production reserves, 2020)
The object of the research is the processes of adhesion structural parts of integral and semi-rigid covers with bookbinding adhesives using continuous and discrete methods of applying adhesive. The conducted experimental studies are based on the use of a comparative technique for measuring the rigidity of double glued and double without adhesion binding materials by determining objective indicators of destructive pressure. The main assumption of research is that the use of various types of bookbinding adhesives applied in continuous and discrete layers will contribute to the formation of additional structural strength of the produced covers. This can’t be achieved without analysis and selection of adhesive polymer compositions from those widely used in bookbinding processes, taking into account the structural strength of the covers acquired after adhesion with these compositions. It is proposed to use fragments of integral and semi-rigid covers, made of high-quality coated papers of various weights, in an amount sufficient to obtain the confidence indicators of the study. As a result of experimental studies of glued coated paper samples, an increase in the relative indicators of structural strength is revealed, caused by the physicochemical effect of various types of adhesives. The features of the application of adhesive polymer compositions on the glued fragments of covers by continuous, tape and checkerboard methods are revealed. Analysis of double glued with a continuous layer of cover fragments, in comparison with double non-glued fragments, showed a significant increase in the relative structural strength of the glued fragments in a wide size range. It is determined that the discrete commensurate deviation of the obtained indicators is caused by the properties used for the research of adhesives. Comparative analysis of glued fragments of covers by tape and checkerboard methods of adhesion application revealed a significant difference in the experimental strength indicators obtained, towards a significant advantage of the checkerboard method. This, in addition to ensuring the structural strength of the glued fragments of the covers, close to the continuous method of applying the adhesion, contributes to a significant reduction in its expenditure component. The results of studies to determine the influence of a sample of binding adhesives, common in the technological processes of manufacturing book products, on the structural strength of integral and semi-rigid covers, to contribute to the planning of resource-saving technological processes.